2015
DOI: 10.2147/ijn.s81263
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-responsive nanocomposites for wound infection prophylaxis in burn management: in vitro evaluation of their compatibility with healing processes

Abstract: Responsive, theranostic nanosystems, capable of both signaling and treating wound infections, is a sophisticated approach to reduce the most common and potentially traumatizing side effects of burn wound treatment: slowed wound healing due to prophylactic anti-infective drug exposure as well as frequent painful dressing changes. Antimicrobials as well as dye molecules have been incorporated into biodegradable nanosystems that release their content only in the presence of pathogens. Following nanocarrier degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Among them, is the use of PHMB associated with nanocarriers, on WDs prepared by additive manufacturing and on smart electronic WD platforms. With the exception of electrospun membranes and of a recent PRM (PRM19) that employed PHMB encapsulated in nanoliposomes, the use of nanocarriers in combination with PHMB has been little explored; a small number of studies with PHMB involving nanocarriers exist [212][213][214][215][216], but the resulting nanosystems are yet to be included in membranes. WDs prepared by 3D printing offer on-demand manufacture of WDs with shapes conforming to a particular body location in a particular patient [217][218][219].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, is the use of PHMB associated with nanocarriers, on WDs prepared by additive manufacturing and on smart electronic WD platforms. With the exception of electrospun membranes and of a recent PRM (PRM19) that employed PHMB encapsulated in nanoliposomes, the use of nanocarriers in combination with PHMB has been little explored; a small number of studies with PHMB involving nanocarriers exist [212][213][214][215][216], but the resulting nanosystems are yet to be included in membranes. WDs prepared by 3D printing offer on-demand manufacture of WDs with shapes conforming to a particular body location in a particular patient [217][218][219].…”
Section: Discussionmentioning
confidence: 99%
“…PHMB-based antiseptics introduce low tissue-toxicity, whereas other antiseptics (e.g., PVP-I and octenidine) have significant impact on cell viability 106 (although other studies have shown low cytotoxicity of HOCl to cells 107 ). Laboratory studies have shown that PHMB (or solutions containing PHMB) affect cells in a variety of ways in terms of cytotoxicity: several studies show no or low-level cell cytotoxicity 106,[108][109][110] whilst others show significant levels of toxicity to cells. 111 Kramer al (2019) 104 comparing an extensive number of antiseptics for the antibacterial activity against test organisms and assessing the cytotoxicity on cultured cells found that PHMB was one of the most suitable antimicrobial agents for use wound antisepsis.…”
Section: Broad-spectrum Efficacy Of Phmbmentioning
confidence: 99%
“…No cytotoxicity was seen towards 3T3 fibroblasts, while good anti-bacterial and anti-inflammatory effects were observed (the latter due to TA-induced inhibition of NO generation in activated human macrophages). Grützner et al [301] studied the effect of enzyme-sensitive antimicrobial nanoplatforms loaded with polyhexanide biguanide (cationic polymer) and octenidine (cationic surfactant) for prophylaxis against infection in cutaneous burns. The results showed time-dependent cellular uptake, along with no major effect on expression of cytokines and pro-inflammatory molecules by endothelial cells, insignificant cytotoxicity compared to solutions of antiseptic agents, and no inhibition of angiogenesis.…”
Section: Nanotechnology For Treatment Of Burn Infections and Woundmentioning
confidence: 99%